The Effect of Giberelic Acid (GA3) and Auxin (IBA) Consentration on Vegetative Growth of Shallot (Allium ascalonicum Var. Lokananta) in The Production System for True Shallot Seed (TSS) - NURAENI (nim : 11413042), DEDE
Shallot (Allium ascalonicum L.) is an important food commodity in Indonesia because of its use can not replaces (non-subsidized use). In the period of 1981-2014, shallot demand increased with an average growth of 8,69% kg/cap/years. However, The average production of shallot in 2010-2014 has decreased to 5,74% per year. In general, farmers in the area of Indonesia are still using conventional cultivation techniques with bulbs as the main seed source in shallot cultivation. Bulbs as the main seed has many deficiences in terms of quality. Therefore, a qualified seed source such as seeds TSS (True Shallot Seed) is needed to improve the shallot cultivation system with the addition of external plant hormon or plant growth regulator (ZPT). At a certain concentration, ZPT is known had to increase the growth and yield of plants. Research was conducted for 6 months and carried out at experimental land of PT. East West Indonesia, Desa Tugu III, Lembang-West Java. This research aims to determine the effect of giberelic acid (GA3) and auxin (IBA) concentration as well as the interaction between giberelic acid and auxin on vegetative growth of shallot plant by using randomized block design with factorial pattern, the first factor is giberelic acid concentration/-GA3 (G) which consist 5 (five) levels that g0 = GA3 0 ppm (control), g1 = GA3 100 ppm, g2 = GA3 200 ppm, g3 = GA3 300 ppm, g4 = GA3 400 ppm. The second factor is concentration of auxin/-IBA (I) which consist 4 (four) levels that i0 = IBA 0 ppm (control), i1 = IBA 50 ppm, i2 = IBA 100 ppm, i3 = IBA 150 ppm, and i4= IBA 200 ppm, each treatment was repeated 3 times. The observed growth variables included: plant height, number of leaves, number of tillers, wet weight of plant, dry weight of the plant, and shoot root ratio, analyzed using two-way ANOVA and DMRT at 95% confidence level to know test. The results showed that no interaction between auxin and giberelin on vegetative growth of shallot plants. The concentration of auxin (150 ppm IBA) gave significant effect on fresh weight per plant.